Managing the Data Effectively Using Object Relational Data Store - Sivagamasundari, T. (Asian Journal of Engineering and Applied Technology, 2017)
The collection of interrelated data, usually referred to as the database, contains information relevant to an enterprise. The primary goal of Database Management System is to provide a way to store and retrieve database information that is both convenient and efficient. Management of data involves both defining structures for storage of information and providing mechanisms for the manipulation of information. A relational database consists of a collection of relations, each of which is assigned a unique name. The relational database contains a set of objects used to store, access, and manage data. The set of objects includes tables, views, indexes, aliases, distinct types, functions, procedures, sequences, and packages Managing the data effectively using Object Relational Data Store (ORDS) is a Object Oriented Relational Database. It provides object oriented enabled features. It ensures the safety of information stored, despite system crashes or attempts at unauthorized access. If data to be shared among several users, the system will avoid possible anomalous results. It is designed to perform very well with most typical SQL operations.